2010
DOI: 10.1007/s11027-010-9223-4
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater harvesting technologies and practises in rural Uganda: a case study

Abstract: Adoption, Education, Information flow, Rural household, Subsidy, Water supply,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
4
22
0
2
Order By: Relevance
“…This could be attributed to the high initial investment costs required especially for the large storage volume. Baguma and Loiskandl [41] concluded that subsidy provision is statistically significant in determining adoption of formal rain water technologies in rural Uganda. The investment costs for informal systems is low because storage facilities range from sauce pans, jerry cans, fabricated containers, drums and other locally made containers which are often already available in the home or are cheap to purchase (refer to Figure 4b).…”
Section: Rainwater Harvesting Practices and Technologiesmentioning
confidence: 99%
“…This could be attributed to the high initial investment costs required especially for the large storage volume. Baguma and Loiskandl [41] concluded that subsidy provision is statistically significant in determining adoption of formal rain water technologies in rural Uganda. The investment costs for informal systems is low because storage facilities range from sauce pans, jerry cans, fabricated containers, drums and other locally made containers which are often already available in the home or are cheap to purchase (refer to Figure 4b).…”
Section: Rainwater Harvesting Practices and Technologiesmentioning
confidence: 99%
“…Without access to a loan, RWH is often unaffordable to an individual farmer ; the limit of extension, credit, and assistance will also hamper the adoption of an RWH system . Baguma and Loiskandl (2010) showed that a subsidy provision was statistically significant for the adoption of RWH technologies in rural Uganda. Several countries, such as in Spain, Brazil, and Australia, also have tried to provide a subsidy when adopting RWH technology for domestic (Domenech and Sauri, 2011).…”
Section: Adoptionmentioning
confidence: 99%
“…As opposed to regulations that require compliance, subsidies target individuals with an appreciation for GI practices and provide an incentive for them to pursue GI implementation (Domenech and Sauri 2011). Baguma and Loiskandl (2010) found citizens were more likely to implement, adequately maintain and operate GI facilities, when subsidies were awarded for specific aspects of the installation, than if cash subsidies were offered.…”
Section: Cost-benefit Indexesmentioning
confidence: 99%